Tick-borne infections in the Leningrad oblast: incidence and seroprevalence - I. A. Karmokov; E. G. Riabiko; R. R. Baimova; L. V. Buts; E. S. Khalilov; D. I. Grechishkina; I. S. Lyzenko; I. A. Bachinin; N. K. Tokarevich (Журнал инфектологии)
The study’s objective was to reveal trends in infections transmitted by ixodes ticks epidemic processes and the level of seroprevalence of the population to the tick-borne encephalitis virus, Borrelia burgdorferi sensu lato, Coxiella burnetii, Anaplasma phagocytophilum and Ehrlichia chaffeensis/ E. muris in the Leningrad Oblast.Materials and methods. A retrospective epidemiological analysis of the tick-bite incidence rate, the ixodic tick-borne borreliosis, tick-borne encephalitis, Q fever, human granulocytic anaplasmosis and human monocytic ehrlichiosis incidence rates, as well as vaccination against tick-borne encephalitis of the population of the Leningrad Oblast in 20112020. The official data of the tick-bite incidence rate, infections transmitted by ixodes ticks incidence rates and vaccination of the population was taken from the forms of federal statistical observation No. 2 and No. 5. Blood was sampled in 2019-2020 from randomly selected donors. Blood serum samples were examined by enzyme-linked immunosorbent assay for the presence of IgG antibodies to the pathogens of the studied infections using commercial test systems according to the manufacturer’s instructions.Results. In the Leningrad Oblast, in 2011-2020, there was a downward trend in the tick-bite incidence rate, as well as in the incidence rates of infections transmitted by ixodic ticks. The long-term average tick bite incidence rate was 369.0. The long-term average incidence rate of ixodic tick–borne borreliosis was 4.1; tick–borne encephalitis was 1.4; Q fever was 0.02. During the analyzed period, no cases of human granulocytic anaplasmosis and human monocytic ehrlichiosis were reported. The seroprevalence to tick-borne encephalitis virus was 1.7%; to B. burgdorferi s. l. – 3.7%; to C. burnetii – 1.8%; to A. phagocytophilum – 1.0%; to E. chaffeensis/ E.muris – 3.2%.Conclusion. The results obtained indicate the existence of active natural foci of infections transmitted by ixodes ticks, fairly frequent contact of the residents with these foci, and possible significant hypodiagnosis of these infections in the Leningrad Oblast.